Los regímenes de tenencia en Galicia (España): el caso de las provincias interiores - Torres Luna, María Pilar de; Lois González, Rubén Camilo (Investigaciones Geográficas, 1992)
The provinces of Lugo and Ourense are the most rural of Galicia. With the study of the land possesion, we check the prevalence of the “property owner” in our country. The last decades this prevalence becomes more established.